DETERMINAN KETIMPANGAN PEMBANGUNAN EKONOMI DI KABUPATEN DAN KOTA PROVINSI KALIMANTAN TIMUR - Mukhammad Syarifudin Hidayatullah Handoko; Wahyu Hidayat Riyanto; Yunan Syaifullah (Jurnal Ilmu Ekonomi, 2020)
The purpose of this research is to know the influence of investment and regional expenditure on economic development disparity between Regencies and Cities in East Borneo Province during the period 2013-2018. The number of samples used 9 regencies/cities. The method used is a quantitative approach using panel data regression analysis technique. Data is processed through E-Views. Based on the research, it was found that the value of inequality that occurred in the districts and cities of East Kalimantan in 2013-2018 was classified as low, where the highest inequality value was 0.33 which occurred in the city of Samarinda which is the capital of the province of East Kalimantan, this value is low. The result showed that simultaneously investment and regional expenditure variabel had a positive and significant effect on the level of economic development inequality, as well as partially investment and regional expenditure variables had a positive and significant effect on the level of economic development inequality between regency and city of East Borneo Province during period 2013-2018.